2011
DOI: 10.5547/issn0195-6574-ej-vol33-no1-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Unity: An Empirical Analysis of Electricity Deregulation in Indian States

Abstract: As developing countries seek to improve their economic prospects, electricity reform has been widely viewed as a central part of this effort. While the focus of most research to date has been at economy or utility level, there has been much less research on regional outcomes. India presents a unique case, as its states share a common economic and political system, whilst having been given considerable flexibility in how they implement reform, thus allowing a comparative analysis of alternative approaches to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 40 publications
2
49
3
1
Order By: Relevance
“…The South African economy will only grow with an available, reliable and secure supply of electricity, which reforms and restructuring of the ESI will provide. This is backed by research conducted by Sen & Jamasb [63] who conclude that industrial consumption has shown a tendency to increase with the implementation of a complete reform of the electricity sector. There is consensus that reforms and restructuring can bring about greater private sector involvement with enhanced total system efficiencies, which is a view that is also taken by Bacon [10].…”
Section: F: Addressing Municipal and Distribution Issues In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The South African economy will only grow with an available, reliable and secure supply of electricity, which reforms and restructuring of the ESI will provide. This is backed by research conducted by Sen & Jamasb [63] who conclude that industrial consumption has shown a tendency to increase with the implementation of a complete reform of the electricity sector. There is consensus that reforms and restructuring can bring about greater private sector involvement with enhanced total system efficiencies, which is a view that is also taken by Bacon [10].…”
Section: F: Addressing Municipal and Distribution Issues In South Africamentioning
confidence: 99%
“…However, no specific recommendation is made for a full ISMO model, and considers REDs viable. Current findings point that regional distributors will not be practical in the short-to-medium term due to political and economic factors Sen & Jamasb [63] Panel empirical data spanning 1991-2007, using dynamic panel data estimators and conducting an econometric analysis of set hypothesis Results show that individual reform measures have affected key economic variables differently. Findings suggest that due to political economy factors, outcomes have tended to be adverse in initial stages of reform but may improve as reform progresses beyond "baseline" structural reforms Findings in this paper reach similar conclusions that electricity tariffs are not foreseen to improve during the initial stages of ESI reforms and restructuring in the short-to-medium term  Pollitt [46] Evidence-based literature assessment of various empirical econometric studies, case studies and industry publications This research concludes that evidence points to ownership unbundling of transmission being a key part of energy market reform in the most successful reform jurisdictions Findings in this paper agree and recommend a total unbundling of transmission assets from the incumbent vertically-integrated utility, thereby increasing system efficiency and non-discriminate access to the grid…”
Section: F: Addressing Municipal and Distribution Issues In South Africamentioning
confidence: 99%
“…Another risk factor relates to political economy issues, where politicians (and state-controlled utilities) have incentives to forego electricity export in favor of securing reliable power supply for domestic agricultural or industrial projects. For example, it is documented that in South Asia during election season state-or municipal-run utilities may have strong incentives to allocate their excess capacities for the needs of local agricultural consumers (who are highly organized, active, and carry significant weight in state elections) instead of selling them across the border (see e.g., Joseph 2010, Sen andJamasb 2012). Another example is a recent collapse of the planned development of a 5,000 MW hydropower project by Western Power Corridor (Westcor), a venture comprising five African countries.…”
Section: Introductionmentioning
confidence: 99%
“…A well known problem of many developing countries is the deficient electric power infrastructure, characterized by low access to electric grid, unreliable power supply, inefficient generating capacities, poor maintenance, and losses in transmission and distribution , Foster and Steinbuks 2009, Sen and Jamasb 2012. Integration of electricity markets is frequently seen as a low-hanging fruit of improving the performance of these deficient systems, especially in a large number of developing countries, where standard textbook recipes of deregulation, privatization, and gradual creation of fully functioning wholesale and retail electricity markets are difficult, if not impossible, to implement in near decades (Besant-Jones 2006, Gratwick and Eberhard 2008, Joskow 2008, Kessides 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, useful to revisit the experience of the process and impacts of this trend and draw out lessons in the aftermath of this experiment. In general, successful electricity reforms should enhance the efficiency of the sector, improve electricity access and reliability, improve service quality, reduce the price-cost gap through cost-reflective pricing and increase investments (Sen and Jamasb, 2012).…”
Section: Introductionmentioning
confidence: 99%